INVENTARISASI JENIS IKAN YANG TERTANGKAP DI BEBERAPA PERAIRAN DANAU DI WILAYAH KECAMATAN KAMIPANG KABUPATEN KATINGAN KALIMANTAN TENGAH - Mardani Mardani; Arthur Mangalik; Yusurum Jagau; Jamzuri Hadie (Universitas Lambung Mangkurat, 2013)
Danau Purun, Danau Jalan Pangen and Danau Kamipang are some of lakes located in Kamipang Sub-district, Katingan Regency, Central Kalimantan. Those lakes are the places to make a living for local people in fulfilling their needs, especially of fish, which is still conducted effectively. However, the people generally tend to desire the business pattern directly giving the yield like capturing fish by using electricity and potassium. The excessive fish capturing business results in the decline of fish population. The objectives of the inventory were to find out the description of how many species of fish population which were alive or survived, and to analyze the water quality and aquatic plants as the supporting capacity of lake waters. The sample collections employed sampling methods on each lake, which were conducted in the morning and afternoon. The instruments and media were gill nets, fishing nets, lalangit, bubu and ancau. The fish sample and alcohol were 70% and 95%. The fish was identified and processed in tabulation. The water quality was measured by applying Horiba Water Checker U-10, Secchi dish and Laboratory Test.